Finland and Its Northern Peers in the Great Recession - Paavo Suni; Vesa Vihriälä (The Research Institute of the Finnish Economy (ETLA), 2016)
The report focuses on the relative macroeconomic performance since the global financial crisis of six Northern European countries with a special emphasis on Finland. While fiscal and monetary policies have definitely impacted on macroeconomic outcomes in the six countries examined, as a whole they do not appear to be the key driving forces of the differences observed between the countries. The initial vulnerabilities, the nature of shocks and the resilience of the economies appear more important in explaining the differences. In particular, the weakness of growth in Finland can best be explained by a series of exceptional negative shocks in combination with a too weak capacity of the economy to improve its cost competitiveness in the absence of exchange rate flexibility.
Keywords: F45; F47; E63; E65; P52; 330; Macro economy; Fiscal policy; Monetary union; Competitiveness; Finland; Wirtschaftswachstum; Internationaler Wettbewerb; Geldpolitik; Finanzpolitik; Finanzkrise; Vergleich; Finnland; Dänemark; Deutschland; Großbritannien; Niederlande; Schweden